Tindak Tutur Ujaran Kebencian di Twitter (X) - Lusi Lian Piantari; Era Bawarti (UniversitasAl Azhar Indonesia, 2025)
Interactions on social media are currently intensified, often leading to conflict. These conflicts often arise because interaction patterns on social media differ from typical spoken and written interactions. This study examines how language users express hate speech on social media, particularly Twitter (X). This phenomenon is known as hate speech. This study aims to describe the types of speech acts that appear in hate speech on Twitter (X). The research method used is a qualitative descriptive method with a pragmatic approach. Data were analyzed using speech acts and hate speech theory. Data were taken from tweets responding to three provincial accounts in Indonesia regarding the performance of regional heads between June and October 2022. The results showed that the types of speech acts encountered were expressive (blaming and asking) and directive (demanding and ordering). Meanwhile, the forms of hate speech found were provocation and insults. The results of the data analysis indicate a relationship between the type and function of speech acts and the form of hate speech.Keyword: directive speech acts, expressive speech acts, hate speech, Twitter (X)